Expected and Experienced Social Impact of Host Residents During Rugby World Cup 2019: A Panel Data Approach - Oshimi, Daichi; Yamaguchi, Shiro; Fukuhara, Takayuki; Taks, Marijke (Frontiers in Sports and Active Living, 2021)
Most social impact research considers the pre- and post-event social impacts of sporting events to investigate the effects of these events on residents’/consumers’ intention/attitude. This study focused on the qualitative differences between pre-event expected social impacts (T1) and post-event experienced social impacts (T2) and investigated viewing behavior as a result of expected social impacts, and intentions to support events from experienced social impacts. The Rugby World Cup 2019 in Japan provided the context for the study. Panel data were collected from the same Tokyo residents in T1 (three months before) and T2 (four months after). The Internet-based survey consisted of six social impact constructs, framed as expectations in T1 and experiences in T2. Both dependent variables, viewing behavior and supporting events, were measured in T2, after the event occurred. Two expected impacts had a significant positive association with viewing behavior, while three experienced social impacts had a significant positive association with event support intention. The main contribution of this article is extending the understanding of the role of social impact as a predictor variable for residents’ behavior and intention to support events by using panel data, which enabled the authors to obtain more robust results. The current research extends the knowledge on consumer expectancy role and social exchange theory in the context of the social impacts of sporting events.